Friedrich Rosen Orientalist Scholarship and International Politics - Theilhaber, Amir (De Gruyter, 2020)
Diplomat, Orientalist, and German foreign minister: Friedrich Rosen (1856-1935) was an Orient expert par excellence in the age of German imperialism. His story is told here for the first time. Following his rise to the centres of international politics and Orientalist scholarship, this study argues that power and knowledge sustained, challenged and subverted each other.